The Influence of Individual Characteristics and Job Characteristics on Employee Performance at the Regional Personnel and Education and Training Agency of Bima Regency - Adriansyah; Kartin Aprianti; Rahmatia (CV Edujavare Publishing, 2026)
This study aims to analyze the influence of individual characteristics and job characteristics on employee performance at the Regional Personnel Agency and Education and Training (BKD and Diklat) of Bima Regency. The study used a quantitative approach with an associative research type. The study population was 75 employees, while the sample was 64 respondents determined using a purposive sampling technique. Data were collected through a questionnaire with a Likert scale and analyzed using multiple linear regression. Before testing the hypothesis, validity, reliability, and classical assumption tests were conducted, including tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. The results showed that individual characteristics had a positive and significant effect on employee performance. Conversely, job characteristics did not have a significant effect on employee performance. However, simultaneously, individual characteristics and job characteristics had a significant effect on employee performance. These findings indicate that employee abilities, skills, motivation, and initiative are important factors in improving organizational performance. Therefore, BKD and Diklat of Bima Regency need to strengthen employee competency development and implement more effective work arrangements to support sustainable performance improvement.